Saberes e práticas da Escola Municipal de Educação Infantil e Ensino Fundamental Santa Luzia (EMEIFSL) da Aldeia Indígena de Muratuba Alto Tapajós, Pará - SILVA, Franciana Fernandes da (Universidade Federal do Oeste do Pará, 2024)
The respect for cultural values and the use of mother language are proper learning processes that allow indigenous peoples to have official tools for the struggle for a specific education. In this study, the objective was to highlight the process of ethnogenesis in the Muratuba village, to demonstrate the functioning of the Municipal School of Early Childhood Education and Elementary Education (EMEIFSL) and to investigate and discuss how traditional knowledge is passed through the classroom through Nheengatu language and the discipline of Notary Saber (traditional knowledge). This study was constructed from a qualitative research. The data was collected from May to June of 2017, through a recorded interview. It is a methodological form that consists in recorded interviews of facts about lived events. Verena Alberti based on a script of questions previously elaborated. Regarding the ethical aspects, the participants signed the Clarified and the Letter of Free Assignment of Oral Deposition Rights. The results show that the Muratuba village experiences a resurgence of ethnic identity (ethnogenesis). (VAZ FILHO, which is marked by an intense process of innovation. In this context, the school does not only teach school knowledge such as scientific knowledge, and the Portuguese language spoken in Brazil, but now they have put as pedagogical proposal the own local cultural knowledge.